2022
DOI: 10.1186/s12961-022-00916-0
|View full text |Cite
|
Sign up to set email alerts
|

Can healthy ageing moderate the effects of population ageing on economic growth and health spending trends in Mongolia? A modelling study

Abstract: Background Population ageing will accelerate rapidly in Mongolia in the coming decades. We explore whether this is likely to have deleterious effects on economic growth and health spending trends and whether any adverse consequences might be moderated by ensuring better health among the older population. Methods Fixed-effects models are used to estimate the relationship between the size of the older working-age population (55–69 years) and economic growth from 2020 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Of course, it is not inevitable that population aging increases provincial health expenditures. Williams et al (2019) find evidence that population aging is not an important driver of health expenditure growth. And as CIHI (2021b) notes, the share of Canada's population age 65 and older rose from 14 to 18 percent over the past decade, although the share of public health expenditures accounted for by this group increased from 44.5 percent to 45.1 percent.…”
Section: Current Challengesmentioning
confidence: 88%
“…Of course, it is not inevitable that population aging increases provincial health expenditures. Williams et al (2019) find evidence that population aging is not an important driver of health expenditure growth. And as CIHI (2021b) notes, the share of Canada's population age 65 and older rose from 14 to 18 percent over the past decade, although the share of public health expenditures accounted for by this group increased from 44.5 percent to 45.1 percent.…”
Section: Current Challengesmentioning
confidence: 88%
“…Rechel et al argue that the high costs associated with older people are caused by the fact that these are more likely to die within a year, when compared to younger people [27]. Recent studies by Raitano and Williams et al also confirm that aging is not a primary driver of health expenditure [11,12].…”
Section: Plos Onementioning
confidence: 99%
“…However, eventually, researchers included various non-macro-economic explanatory variables of PHE. Aging was given particular attention by researchers as they tried to understand whether demographic changes affect PHE [11,12]. Attention was also given to the political influences, such as type of government composition, year in government, political ideologies and years of election [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Economic modelling techniques were applied to analyse the effects of age and demographic structure on trends in health expenditures and the moderating effect of improved health in the older working-age population in six countries in WHO's Western Pacific Region. The paper presented in this supplement describes the simulation results for Mongolia, which suggested that good health at older ages could moderate the potentially negative effects of population ageing on economic growth and health spending [30]. This study sends an important message to policymakers who are concerned about decreased revenue and increased health expenditures due to population ageing: these consequences are not inevitable, but rather they can be significantly mitigated or altered by making policy choices that enable older people to live in good health.…”
Section: Research To Accelerate Uhc In the Context Of Global Populati...mentioning
confidence: 99%